ANALISIS TERHADAP PERKAWINAN BEDA AGAMA DITINJAU DARI PERATURAN PERUNDANG UNDANGAN DI INDONESIA (Studi Kasus Penetapan 278/Pdt.P/2019/PN.SKT) - Mohammad Rifqy Fakhriza; Mia Hadiati (Fakultas Hukum Universitas Tarumanagara, 2021)
The life of society has evolved, there are no boundaries between people from any race, religion, tribe background in Indonesia. Because of that, it's very possible for people from two different religions to have any relationship and want to get married. One of those people is Agustinus Dwi Nugroho and Ika Dede Yuniar, they appeal some pleas to Surakarta Court, demanding for their marriage to be legalized. In the verdict, the judge granted all the pleas. The issue in this research is how is different religion marriage in Indonesian laws? (Case Studies number 278/Pdt.P/2019/PN.Skt), the research method is Normative with conceptual, laws and case approach and supported by data from library and some interviews. Different religion marriage in Indonesian law is not yet being regulated but there are a few laws related to the topic, such as: Article 2 Paragraph (1) and Article 8 Law Number 16 Year 2019, Article 35 Law Number 23 Year 2006, and Article 40 and Article 44 in Islamic Law Compilation. In the verdict that became the subject in this research, the writer feels there's some law that is not yet included in the consideration, such as Article 8 Law Number 16 Year 2019 and Article 44 in Islamic Law Compilation because one of the parties in that verdict is moslem.